Deteksi Dini Varian Covid-19 Dengan Metode CBR-AHP Dan Sorgenfrei - Mohamad Riza Darmawan; Setyawan Wibisono (STEKOM PRESS, 2022)
The case fatality rate caused by Covid-19 in Indonesia is around 2.9%. The death rate by age group is from all Covid-19 patients who died, including 0.5% aged 0-5 years, 0.5% aged 6-18 years, 2.8% aged 19-30 years, 12.7 % were aged 31–45 years, 36.8% were aged 46–59 years, and 46.7% were aged 60 years and over. With the large number of cases that occurred in Indonesia, it turned out to be due to the lack of proper handling of the early symptoms of the Covid-19 virus. To overcome this, it is needed as a tool for early detection of the Covid-19 variant by using the CBR-AHP expert system with the Sorgenfrei algorithm. The results of the consultation for the early detection of the Covid-19 variant were obtained from the highest similarity value of Sorgenfrei. Of all the variants found above, the highest similarity value of Sorgenfrei is Omicron with a similarity of 1,000. Omicron has the highest value because it has a value of a, which is the same symptom between old cases and large new cases.